2017
DOI: 10.1111/ffe.12760
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the plastic zone near the crack tips under the uniaxial tension using ordinary state‐based peridynamics

Abstract: In this paper, the plastic model of ordinary state‐based peridynamics is established. The size and shape of plastic zone around crack tips with the different inclination angles are simulated using ordinary state‐based peridynamics. Comparison of the size and shape of plastic zone around the crack tips obtained from peridynamic solution and analytic solution is made. It is found that the relative errors between the analytical and peridynamic solution are very little. Therefore, it is feasible to predict the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…For elastoplastic behavior, OSB-PD models have been introduced in (Madenci and Oterkus, 2016;Mitchell, 2011;Silling et al, 2007). Several 2D versions of this theory appeared in (Madenci and Oterkus, 2016;Pashazad and Kharazi, 2019;Zhou et al, 2018).…”
Section: Significance and Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…For elastoplastic behavior, OSB-PD models have been introduced in (Madenci and Oterkus, 2016;Mitchell, 2011;Silling et al, 2007). Several 2D versions of this theory appeared in (Madenci and Oterkus, 2016;Pashazad and Kharazi, 2019;Zhou et al, 2018).…”
Section: Significance and Motivationmentioning
confidence: 99%
“…Another limitation of the models in (Madenci and Oterkus, 2016;Pashazad and Kharazi, 2019) is that they are not valid under arbitrary rigid-body rotations (Le and Bobaru, 2018;Madenci, 2017). Estimation of the plastic zone near the crack tips in rocks was studied in (Zhou et al, 2018) using a 2D OSB-PD model. The 2D formulation in (Zhou et al, 2018), adopts the 3D formulation suggested in (Mitchell et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The SB‐PD formulation can be classified into the ordinary state‐based peridynmaics (OSB‐PD) 12,13 and non‐ordinary state‐based peridynmaics (NOSB‐PD), 14–17 according to whether the force density vector state is parallel to the deformation vector state. The OSB‐PD is an active area of research and has been a promising framework for modeling various problems 18–22 …”
Section: Introductionmentioning
confidence: 99%